Nanotribology of viruses reveals their adhesion strength and modality of motion on surfaces - Ault, Charles; Simon, Claudia; Tsvetkova, Irina B.; De Pablo, Pedro J.; Dragnea, Bogdan (Frontiers in Biophysics, 2025)
Virus adsorption at solid-water interfaces is an ubiquitous phenomenon in the lifecycle of waterborne viruses, both in natural environments and in engineered systems. Airborne aqueous microdroplets containing viruses readily attach to solid surfaces. Inside the droplet, viruses may adhere to the solid-liquid interface. Investigating virus adsorption at solid-water interfaces could lead to new ways to suppress virus infectivity. To further improve our understanding of virus adsorption, we studied the friction dynamics of icosahedral viruses adsorbed to solid surfaces. Using the lateral torsion of cantilevers in atomic force microscopy to move individual capsids in a liquid environment, we found that the virions tend to roll rather than slide on the surface. In contrast, rigid, ligand-stabilized gold nanoparticles are more likely to combine rolling with sliding under the same conditions. The experiments indicate that the force required to drag the viruses on the surface is four times less than that of AuNPs, while the lateral force work needed to induce virus movement was ∼104 kT, ten times less than that of the rigid gold nanoparticles. These results go beyond the paradigm that adhesion of nanoparticles is mainly governed by geometrical factors, such as size and area of contact, highlighting the need to amend modeling approaches to account for mechanically-compliant tribological response of biologically derived nanoparticles.